Relationship between actigraphy‐assessed sleep quality and fat mass in college students. (25th December 2015) - Kahlhöfer, Julia; Karschin, Judith; Breusing, Nicolle; Bosy‐Westphal, Anja
Abstract : Objective: Only a few studies have used objective measurements to investigate the relationship between sleep quality and obesity. These studies showed controversial results. Methods: Sleep efficiency was measured by Actiwatch 2 in 132 healthy students (age 23.3 ± 3.7 years, BMI 23.1 ± 4.1 kg/m 2 ) for 12 ± 3 nights, differentiating between work and free days. Physical activity, dietary habits, and autonomic function (heart rate variability, HRV) were analyzed as potential determinants of sleep quality and its relationship with body composition. Results: Sleep efficiency was 87.0% in women and 84.9% in men ( P  < 0.05) and was higher at free days when compared to work days in women ( P  < 0.05). Lower sleep efficiency was associated with a higher fat mass. This was true for sleep efficiency on work days in women [fat mass index (FMI): r  = −0.35, P  < 0.01] and for free days in men (FMI: r  = −0.37, P  < 0.05). Poor sleep efficiency was associated with less physical activity ( r  = 0.29, P  < 0.05) and impaired HRV in women ( r  = 0.60, P  < 0.05) and with a higher fat intake in men ( r  = −0.39, P  < 0.05). Conclusions: Poor sleep efficiency was associated with higher fat mass. The relationship between sleep quality and fat mass differs between work and free days and may be explained by physical activity and autonomic function in women and dietary habits in men.